SOSIALISASI PEMASARAN PRODUK UKM KRIPIK KIKIM "JALAL" DI PEKON PODOMORO MENGGUNAKAN MEDIA SOSIAL INSTAGRAM - Muhammad Junaidi; Yuli Krismawati; Sutejo Sutejo; Yuri Fitrian (Jurnal PkM Pemberdayaan Masyarakat, 2021)
Competition in the distribution industry is getting tighter. One of the things that makes a distribution company survive is the provision of products that are on time to consumers at the right time, and at an economical cost. Product availability and economical selling prices can only occur if there is good coordination between the company and the parties in its supply chain. Micro and medium enterprises are part of the national business. UMKM can also be considered as the locomotive of national and regional (regional) economic growth, because they have the potential to empower all available resources and encourage the growth of entrepreneurial development. The role of UMKM in Indonesia, namely increasing employment opportunities, equal distribution of income, rural economic development, increasing non-oil and gas exports and contributing to increasing GDP. On this basis, STMIK Pringsewu students collaborate with Pekon Podomoro to provide assistance services for people who have home industry businesses to have a digital-based sales platform, namely a social media. This activity aims to provide an understanding for UMKM players how to market food products, crafts, clothing, services and others using social media. From this activity, the people of Pekon Podomoro who have a home industry can market their products quickly, precisely and safely so that business actors can provide convenience to customers.